2019
DOI: 10.1097/phh.0000000000001104
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Eating Policy Strategies in Community Health Improvement Plans: A Cross-Sectional Survey of US Local Health Departments

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Those findings were consistent with a 2012 survey of LGs in two US states, demonstrating that larger communities had more policies supporting healthy behaviours than smaller communities 14 . A 2016 US study surveyed Community Health Improvement Plans in local health districts with populations of less than 500,000 residents and found that 32% of surveyed local health districts reported one or more healthy eating policies in their plan 15 . Knowledge of policies for supporting healthy retail food environments is important to establish which action areas are in need of policy development and prioritising resources to support specific LGs, benchmarking of policy best practice, and for ongoing monitoring to assess change over time.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Those findings were consistent with a 2012 survey of LGs in two US states, demonstrating that larger communities had more policies supporting healthy behaviours than smaller communities 14 . A 2016 US study surveyed Community Health Improvement Plans in local health districts with populations of less than 500,000 residents and found that 32% of surveyed local health districts reported one or more healthy eating policies in their plan 15 . Knowledge of policies for supporting healthy retail food environments is important to establish which action areas are in need of policy development and prioritising resources to support specific LGs, benchmarking of policy best practice, and for ongoing monitoring to assess change over time.…”
supporting
confidence: 74%
“…14 A 2016 US study surveyed Community Health Improvement Plans in local health districts with populations of less than 500,000 residents and found that 32% of surveyed local health districts reported one or more healthy eating policies in their plan. 15 Knowledge of policies for supporting healthy retail food environments is important to establish which action areas are in need of policy development and prioritising resources to support specific LGs, benchmarking of policy best practice, and for ongoing monitoring to assess change over time. Although we have previously examined the nutrition-related and obesity prevention policies, practices and attitudes of LGs in the state of Victoria in a survey in 2018, 12 to date, no national studies on this topic have been undertaken in Australia.…”
Section: Local Government Policies On Healthy Food Promotion and Obes...mentioning
confidence: 99%
See 2 more Smart Citations
“…Communities and LHDs are increasingly engaging in population health activities, including health improvement planning, potentially due to benefits such as reductions in diabetes and cardiovascular disease mortality (15,16). Although most CHIPs generally address nutrition and PA, emerging evidence suggests that strategic health improvement plans underutilize PSE strategies to address HE and PA (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%